Relationship between body composition and upper limb physical fitness among Chinese students: 4-Year longitudinal follow-up and experimental study - Wang, Qingmei; Qian, Junwei; Pan, Haoran; Ju, Qianqian (Frontiers in Physiology, 2023)
Background: Recently, students’ fitness has been declining, and high physical fitness level is crucial in establishing optimal physical/mental health and academic performance. The purpose of this study was to explore the relationship between body composition and upper limb physical fitness and the specific aspects of low physical fitness level in Chinese students. Exploring the development and impact factors for upper limb physical fitness can provide a theoretical basis for the health management strategy of students. Methods: Study 1 collected data from 183 students over 4 years and used Hierarchical Linear Model (HLM) to explore the quadratic predictive role of body composition on upper limb physical fitness. To further explored which aspects of upper limb physical fitness were affected by body composition, study 2 conducted an experimental investigation among 42 students, comparing different kinds of upper limb physical fitness within two different body composition groups. Results: Studies found (1) from 2015 to 2018, students’ Body‐Mass‐Index (BMI) showed an upward trend, and BMI differences were significant from year to year. While the upper limb physical fitness showed a downward trend. There were significant differences in the number of pull-outs between 2015 and 2016, 2015 and 2017, and 2015 and 2018. (2) The quadratic term of BMI could predict the upper body physical fitness in the same year and the following year. That is, when BMI was medium, the upper body fitness of the same year and the following year was the best. (3) Chinese students with excellent body composition had greater grip strength, drape height and anaerobic power than those with average body composition. Conclusion: In recent years, students’ BMI has been increasing, and the upper body physical fitness has been decreasing. Furthermore, body composition can predict the upper body mass in the same year and the second year, and students with better body composition also had greater grip strength, drape height and anaerobic power in their upper limbs.